Functional Properties of Vinegar - Budak, Nilgün H; Aykin, Elif; Seydim, Atif C; Greene, Annel K; Guzel‐Seydim, Zeynep B (Journal of food science, 2014)
A variety of natural vinegar products are found in civilizations around the world. A review of research on these fermented products indicates numerous reports of health benefits derived by consumption of vinegar components. Therapeutic effects of vinegar arising from consuming the inherent bioactive components including acetic acid, gallic acid, catechin, ephicatechin, chlorogenic acid, caffeic acid, p‐coumaric acid, and ferulic acid cause antioxidative, antidiabetic, antimicrobial, antitumor, antiobesity, antihypertensive, and cholesterol‐lowering responses. The aims of this article are to discuss vinegar history, production, varieties, acetic acid bacteria, and functional properties of vinegars.